Volatility Estimation Of Islamic and Conventional Stock Prices Using GARCH Method - Abd Manaf, Nur Hidayah; Ismail, Isaudin (Enhanced Knowledge in Sciences and Technology, 2022)
Volatility estimation of the Islamic and conventional stock prices brings significant in investment. Hence, this study focused on modelling in financial and it is one of factors that have effect on volatility, persistency and performance of their portfolio management. This study aimed to observe the stock prices trend, volatility and persistency of the Islamic and conventional stock prices in Malaysia. This objective can be achieved by selecting and applying ARCH and GARCH to investigate the behavior of stock return volatility for Petronas Gas, AXIATA Group, Public Bank and Malayan Bank covering the period from October 2007 until October 2021. The main findings. the model from GARCH family models. Incorporating the proposed volatility model of this study can significantly improve the investor’s view towards these two stock prices which is Islamic and conventional stock prices.